A Conceptual Methodology of Integration of Islamic Perspectives into the Curriculum: Using Medical Imaging as an Example - Zainuddin, Zainul Ibrahim (IIUM, 2015)
Integration of Islamic perspectives is already evident in various fields that include among others, Art, Medicine, Engineering, Sociology and Human Sciences. However, there are hardly any Islamic viewpoints in the present literature used for teaching and learning Medical imaging. To do the same for Medical imaging will not only complement the other efforts but also enrich the Islamic educational environment. Thus, this paper presents a conceptual approach towards integrating Islamic perspectives in the Medical imaging curriculum. The objective of the integration is to introduce, mould, remind and enhance the necessary Islamic attributes to the graduates. Internalisation and manifestation of those attributes in their future professional lives could become a catalyst towards promoting and propagating the concept of model Muslim Medical imaging practitioner. The nature of the Medical imaging curriculum is described as one that addresses areas that involve basic sciences, human interactions, use of technology, cost, safety, professionalism and medical ethics that are unique to the profession. The methodology involves an in-depth examination across a typical Medical imaging curriculum. The identification of the various concepts, topics and sub-topics enables the assimilation of the Islamic perspectives to be made across the four years of studies. A literature search was also performed to identify the Islamic perspectives that are used in previous integration processes. The identified perspectives include Islamic Worldview, teachings from the Holy Qur’an and Hadith, Maqasid and Qawaid Al-Shari’ah, Islamic history and civilisation, Islamic jurisprudence and thoughts of Muslim scholars. This is followed by a brief discussion pertaining to the individual tailoring of their possible applications in the curriculum. It is hoped that the conceptual approach can provide a direction in integration of Islamic perspectives in the curriculum with the intention to enrich the Muslim character in the graduates.